Analysis of Dietary Patterns and Nutritional Adequacy in Relation to Nutritional Status - Rifana Cholidah; Emmy Amalia; Ario Danianto; Dyah Purnaning; Zahro Ananta; Ni Kadek Sintha Amanda (MEDICA (International Medical Scientific Journal), 2026)
University students are vulnerable to unhealthy eating behaviors due to academic demands, time constraints, and reliance on convenience foods, which may affect their nutritional status. This study aimed to assess nutritional status, dietary patterns, and nutritional adequacy among second-semester students at the Faculty of Medicine and Health Sciences, University of Mataram, and to examine their associations. A cross-sectional study was conducted among 215 students. Nutritional status was determined using body mass index (BMI), while dietary intake was assessed through 24-hour food records analyzed using NutriSurvey. Participants had a mean age of 18.81 ± 0.75 years and a mean BMI of 21.83 ± 4.18 kg/m², with 66.51% classified as having normal nutritional status. The study shows that most students have inappropriate dietary patterns (66.51%) and inadequate macronutrient intake, particularly carbohydrates. Although 69.77% achieved adequate total energy intake, the overall dietary pattern reflected an imbalanced macronutrient distribution. No significant association was found between dietary patterns and nutritional status (p = 0.109) or between nutritional adequacy and nutritional status (p = 0.295). These findings suggest that factors beyond dietary intake alone may influence nutritional status among university students. Therefore, targeted nutrition education and behavior-based interventions are needed to promote healthier eating habits among future health professionals.